Anti-Colitic Properties of Linum usitatissimum Alkaloid in Ulcerative Colitis Induced by Dextran Sodium Sulphate in BALB/c Mice - Riad Ferhat; Meriem Aziez; Mohamed Sofiane Merakeb; Rashed N. Herqash; Abdeltif Amrane; Noureddine Bribi (Current Drug Therapy, 2026)
Introduction: Inflammatory bowel disease, encompassing ulcerative colitis and Crohn's disease, represents a growing global health burden, characterised by chronic intestinal inflammation, oxidative stress, and progressive mucosal barrier dysfunction. This study investigated the anti-colitic potential of the whole alkaloid extract of Linum usitatissimum (ALU) in a murine model of dextran sodium sulphate (DSS)-induced colitis, evaluating its antioxidant, anti-inflammatory, and mucosal-protective properties. Methods: Forty male BALB/c mice were divided into five groups (n = 8): vehicle control, DSS-only, and three DSS groups treated orally with ALU at 50, 100, or 200 mg/kg daily. Clinical activity, colon weight-to-length ratio, H&E histological scoring, and biochemical markers (CAT, GSH, NO, MDA) were assessed on Day 7. Results: DSS induced marked colitis, which ALU reversed dose-dependently; at 200 mg/kg, ALU normalised the colon weight-to-length ratio, restored CAT and GSH levels, reduced NO and MDA, and produced near-complete histological recovery. Discussion: The current study demonstrates that ALU has considerable antioxidant and intestinal anti-inflammatory capabilities. The anti-colitic effect was demonstrated through multiple pathways, including maintaining a stable body weight, reducing the colon weightto-length ratio, restoring endogenous antioxidant defenses, and inhibiting pro-oxidant and pro-inflammatory mediators. Conclusion: These findings show that the entire alkaloid extract from Linum usitatissimum seeds significantly reduces inflammation in the DSS-induced colitis model in vivo, showing its potential as an anti-inflammatory drug for the treatment of inflammatory bowel diseases.